1973
DOI: 10.1007/bf02531909
|View full text |Cite
|
Sign up to set email alerts
|

Glycerides, waxes and sterols in ovaries ofAscaris lumbricoides (Nematoda)

Abstract: Glycerides (65%), ascaroside esters (33%), waxes (1.5%) and sterols (0.26%) accounted for essentially all the neutral lipids inA. lumbricoides ovaries. Nineteen per cent by weight of the triglycerides contained only long chain fatty acids. Nearly all the remaining triglycerides contained 1 mol volatile acid. Mono‐ and diglycerides, free fatty acids and triglycerides containing 2 mol volatile acids were present in very small amounts. Mole percentages of glyceride volatile acids were α‐methylavaleric (70), α‐met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…1%. This is in contrast with what was observed in parasitic nematodes, where the ascaroside esters constituted up to 33% of all neutral lipids in the ovaries [9].…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…1%. This is in contrast with what was observed in parasitic nematodes, where the ascaroside esters constituted up to 33% of all neutral lipids in the ovaries [9].…”
contrasting
confidence: 77%
“…The dauer larva induction assay was performed according to [9], with monoascarosyl alkanediol (25 or 250 mg per well) isolated from A. suum.…”
Section: Experimental Partmentioning
confidence: 99%
“…The concentrations of the branched C15 fatty acid, are 1.6 to 2.0% of the total fatty acid in eggs at all stages of embryonation. This observation is consistent with the results previously mentioned by Jezyk (1968) and Tarr and Fairbairn (1973), who reported 1.9% and 1.24% of the fatty acid in ovarian triglyceride of Ascaris him bricoides, respectively. In aerobic conditions, it was observed that the incorporation of radioactivity in C18,1 acid was decreased and that in branched C15 fatty acid was greatly increased in the second stage larvae compared with the first stage larvae.…”
Section: Studies Of Biosynthesis Of Fatty Acids In Ascaris Larvaesupporting
confidence: 94%